Digital Transformation in Civil Servant Competency Development at BPSDMD Banten Province - Budi Sihabudin; Fatulloh Fatulloh; Aisyah Mauliddina (ijd-demos, 2024)
Abstract Digital transformation within the bureaucracy has become an urgent necessity for achieving excellent Electronic-Based Government Systems (SPBE). This study aims to analyze the implementation, obstacles, and impact of digital transformation on the competency development of State Civil Apparatus (ASN) at the Regional Human Resources Development Agency (BPSDMD) of Banten Province. A descriptive qualitative method was employed, utilizing data collection techniques such as in-depth interviews, observation of e-learning platforms, and document analysis. The results indicate that the digitalization of training systems—specifically through the "Banten Ceria" and "SIM Ceria" Learning Management System (LMS) platforms—has significantly improved equitable access, budget efficiency, and flexibility regarding employees' learning schedules. However, the program's acceleration remains hindered by the digital literacy gap across ASN generations (the digital divide) and limited information technology infrastructure in certain remote work units. The study concludes that digital transformation at BPSDMD Banten Province has successfully fostered a more adaptive work culture, although it requires strengthened local regulations and continuous enhancement of digital literacy capacity across all levels of the civil service. Keywords: Digital Transformation; Competency Development; State Civil Apparatus; BPSDMD Banten.